Effect of the alkaline treatment conditions on the tableting performance of chitin obtained from shrimp heads (2014)
ABSTRACT: Chitin is a natural polymer with a potential pharmaceutical application since its exhibits some biodegradability, biocompatibility and relative non-toxicity. It is obtained from crustacean’s exoskeletons by treatment with alkalis and mineral acids followed by a depigmentation step. In this work, the effect of alkaline treatment on tableting properties such as compact tensile strength and disintegration time and other polymer properties, such as acetylation degree and degree of crystallinity was evaluated. A Box Behnken Design with 17 runs, three levels and three factors (that is, reaction temperature at 30, 75 and 100°C, NaOH concentration at 0.5, 3 and 6 M and reaction time at 1, 4 and 8 h) was employed. A combination of a high temperature, alkali concentration and reaction time led to a low chitin yield, reduced its acetylation degree, increased its crystallinity and hence, decreased the tensile strength, but accelerated the disintegration time of compacts. The optimal reaction condition was achieved using an alkali concentration of 2.6 M, temperature of 70°C and a reaction time of 1 h. These conditions rendered compacts with a tensile strength of 2.3 MPa and disintegration of 28.6 min. Therefore, chitin can be used for the preparation of solid dosage forms by direct compression.